Systemic crisis and growth revisited: Has the global financial crisis marked a new era? - Sven Steinkamp; Frank Westermann (Osnabrück University, Institute of Empirical Economic Research, 2018)
Occasional crises have been shown to be part of growth enhancing mechanism (see Rancière, Tornell and Westermann, 2008). In this paper, we document that neither the stereotypical case study of India vs. Thailand, nor the benchmark growth-regression in this earlier research support this result anymore when updating the sample by one decade that includes the Global Financial Crisis, 2007/8. We analyze the time-varying nature of this relationship in rolling regressions and an historical dataset. In the subset of countries with enforceability problems, we find that the link between occasional crisis, measured by the negative skewness of credit growth, and per-capita output growth still remains intact.
Keywords: F34; O43; G01; 330; Long-Term Growth; Systemic Crisis; Financial Liberalization